Speaking for ourselves : women and distance education in India - Kanwar, Asha.; Jagannathan, Neela (New Delhi : Manohar Publishers & Distributors, 1995)
Contributed articles.
Includes bibliographical references (p. 232-241) and index.
Keywords: Distance education -- Cross-cultural studies -- India; Women -- Education -- Cross-cultural studies -- India